Rate of Force Development Is Related to Maximal Force and Sit-to-Stand Performance in Men With Stages 3b and 4 Chronic Kidney Disease - Gollie, Jared M.; Harris-Love, Michael O.; Patel, Samir S.; Shara, Nawar M.; Blackman, Marc R. (Frontiers in Rehabilitation Sciences, 2021)
The primary aims of the present study were to assess the relationships of early (0-50 ms) and late (100-200 ms) knee extensor rate of force development (RFD) with maximal voluntary force (MVF) and sit-to-stand (STS) performance in participants with chronic kidney disease (CKD) not requiring dialysis. Methods Thirteen men with CKD (eGFR=35.1±7.5 ml/min per 1.73 m2, age=70.5±6.4 years) and twelve non-CKD men (REF) (eGFR=80.3±14.8 ml/min per 1.73 m2, age=70.2±2.9 years) performed maximal voluntary isometric contractions to determine MVF and RFD of the knee extensors. RFD was measured at time intervals 0-50 ms (RFD0-50) and 100-200 ms (RFD100-200). STS was measured as the time to complete five repetitions. Measures of rectus femoris grayscale (RF GSL) and muscle thickness (RF MT) were obtained via ultrasonography in the CKD group only. Standardized mean differences (SMD) were used to examine differences between groups. Bivariate relationships were assessed by Pearson’s product moment correlation. Results Knee extensor MVF adjusted for body weight (CKD=17.1±4.1 N∙kg0.67, REF=21.5±5.3 N∙kg0.67, SMD=0.79) and STS time (CKD=15.9±3.4 s, REF=12.2±3.7 s, SMD=1.03) were lower in the CKD group than the REF group. Absolute RFD100-200 was significantly directly related to adjusted MVF in CKD (r=0.56, p=0.049) and REF (r=0.70, p=0.012), respectively. STS time was significantly inversely related to absolute (r=-0.75, p=0.008) and relative RFD0-50 (r=-0.65, p=0.030) in CKD but not REF (r=0.08, p=0.797; r=0.004, p=0.991). Conclusion The results of the current study found that early RFD was associated with STS time in CKD while late RFD was associated MVF in both CKD and REF.